Hubungan Efikasi Diri dengan Perilaku Pencegahan Covid-19 pada Dewasa Muda - Kadek Wahyu Widnyani; I Ketut Gama; I Gusti Ketut Gede Ngurah; Ketut Sudiantara (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
Covid-19 has caused the death of hundreds to millions of people, so Covid-19 prevention behavior needs to be carried out. The way to prevent the occurrence of Covid-19 is to carry out Covid-19 prevention behaviors. Self-efficacy is self-confidence in doing something, high self-efficacy is needed in order to carry out Covid-19 prevention behaviors well. This study aims to determine the relationship between self-efficacy and Covid-19 prevention behavior in young adults in Central Banjar, Sesetan Village in 2022. The type of research used is non-experimental with correlational types and cross-sectional approaches using non-probability sampling with purposive sampling. The total population is 391 people with a sample of 198 people. The study was conducted in April 2022. Data collection using self-efficacy questionnaires and Covid-19 prevention behaviors. The results showed that most young adults aged 21 years (34,8%), female gender (61,1%), college students (42,9%), higher education (63,6%), high self-efficacy (46,5%), good Covid-19 prevention behavior (80,8%). Test the hypothesis using the Spearman test with a value of p = 0,000 (α=0,05) and a value of r = +0,709. Based on the results of the study, it can be concluded that there is a significant relationship between self-efficacy and Covid-19 prevention behavior in young adults in Central Banjar, Sesetan Village (p = 0,000 and r = +0,709) with most who have high self-efficacy with good preventive behavior, meaning that the higher the self-efficacy of young adults, the better the actions they take to prevent the spread of Covid-19.